(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
In the global financial crisis conditions, Vietnam banking sector has suffered from liquidity and deadlock in the operation. Indispensably, evaluation and measurement of performance are an important task for the banks as well as has become a pressing, but many managers agree that their evaluation systems do not adequately fulfill this function. Actually, balanced scorecard (BSC) is a new idea in performance management and applies to evaluate firm or bank performance through finance and non- financial dimensions. The purpose of this study is to determine the factors of BSC actually affecting Vietnamese banks. Besides, to test and generate model which is the best fit model used for the application and implementation BSC. Another purposed of study is to contribute to the understanding of how BSC is developed and applied in evaluating the performance of banks in Vietnam. Based on the concepts of Kaplan and Norton, using the data declare available from the banks, stock market for the financial dimension and survey for non-financial dimension. BSC is derived to evaluating and measuring the performance of the banks in 2015. In the indefectible combination, Structural Equation Modeling (SEM) is employed to test relationships of BSC and firm performance of Vietnamese banks and adopted to verify the goodness of fit effects of measurement model and structural model. The results also indicate that BSC directly and positively influence firm performance of Vietnamese banks. Furthermore, due to lack of research work in this area and the banking sector in Vietnam, this study contributes to the knowledge on how Vietnamese banks may apply the BSC to evaluate their performance and management system. The author proposes some future research needs required in this area. The study also proposes the conceptual framework of the relationship between BSC and the firm performance of Vietnamese banks to direct corporate performance at strategic vision of future research.